A Report on Myelosuppressive and Lymphopenic Effects of Hexavalent Chromium in a Murine Model - N. K. Sarkar, R. R. Ray* and (Journal of Experimental Sciences, 2011)
Both leucocyte and erythrocyte counts of blood sharply decreased in Swiss mice after 2 weeks of intraperitoneal treatment with potassium dichromate (4 mg/Kg for 5 days per week). A marked neutropenia along with a relative rise in lymphocyte count were also noted. Chromosomal abnormalities (chromatid break, ring chromosome formation and aneuploidy) and micronucleus formation were observed in both lymphopoietic and myelopoietic tissues (spleen and bone marrow, respectively). The overall findings indicate that a cytotoxic potential of hexavalent chromium may result in myelosuppression, lymphopenia as well as suppression of erythropoiesis. However, a higher incidence of chromosomal abnormalities and micronucleated cells in the bone marrow than in the spleen suggests hexavalent chromium to be relatively more myelosuppressive than lymphopenic in action.